Desenvolvimento e validação da aplicação Revisanatomy: avaliação formativa com revisão espaçada na anatomia humana - Côrtes, Mayra Aparecida (2024)
This study aimed to develop, validate, and implement a learning object as a web application to support the assessment process in Human Anatomy. The RevisAnatomy application was designed as an educational assessment tool. It incorporates spaced revision and test effect strategies and aims to promote the student's role in the teaching and learning process during formative assessment. This study is applied and methodological with a quasi-experimental design and qualitative-quantitative approach. It was approved by the Research Ethics Committee of the State University of Mato Grosso under CAAE No. 56258122.9.0000.5166. The LORI (Learning Object Review Instrument), the Content Validity Index by Item (CVI-I), the General Content Validity Index (CVI-S), and Cronbach's Alpha Coefficient were used to assess the application's quality, reliability, and validity. The database was built in Microsoft Office Excel, and the statistical analyses were carried out using Jamovi software, version 2.6.3. The System Usability Scale (SUS) and the pre- and post-test scores were used to analyze the tool's implementation. Student perceptions were analyzed using a semi-structured questionnaire. The data were analysed using descriptive and inferential statistics. The descriptive analysis employed measures of central tendency (mean and median) and dispersion (standard deviation and interquartile ranges), depending on the distribution of the variables. The inferential analysis included chi-squared, Fisher's exact and Mann–Whitney tests according to the nature of the data. Academic performance was assessed using mixed ANOVA models and effect size measures were calculated to complement the interpretation of the results. All analyses were performed using R software (v. 4.3.3) with a 5% significance level. The application was validated by 17 judges, including Human Anatomy professors and education and information technology professionals, and by the target audience, which included 07 health students. The judges assessed the application based on specific content, educational quality, design, and usability criteria, obtaining a CVI-S of 0.925, which indicates high agreement. Cronbach's alpha coefficient was 0.838, confirming the instrument's reliability. The study involved 39 health students, who were divided into two groups: a control group (20 students) and an experimental group (19 students). Significant improvements in post-test scores were observed in both the control and experimental groups (5.55 vs. 6.26). However, there was no statistically significant difference between the two groups. The application's usability was considered good (SUS score = 78.8), and it was well accepted by the students. A qualitative analysis of student perceptions, conducted through content analysis with data triangulation, revealed positive aspects related to the application's usability, functionality, and pedagogical impact. These results indicate that the application is a promising tool for supporting learning during formative assessments in human anatomy. It is recommended that its use be integrated with regular assessments and continuous monitoring, in order to strengthen its effects on the teaching and learning process, especially in the context of formative assessment.